REVIEW: TRANSCULTURAL ENCOUNTERS IN THE HIMALAYAN BORDERLANDS - KALIMPONG AS A "CONTACT ZONE" - eviewed by Enrico, Beltramini (Asian Highlands Perspectives, 2018)
Markus Viehbeck (ed.), 2017. Transcultural Encounters in the Himalayan Borderlands - Kalimpong as a "Contact Zone." Heidelberg: Heidelberg University Publishing, viii + 350 pp, ISBN 978-3-946054-58-0 (paperback 55.37USD). This volume is both a story of the hill station of Kalimpong, in the Eastern Himalayan region, and a study of transcultural dynamics seen through the prism of the local story of Kalimpong. A collaborative work, the book is the result of a conference that brought together various international scholars on the cultural history of Kalimpong. Scholars from Europe (Amsterdam, Copenhagen, Heidelberg, Manchester, Oxford, Roskilde), North America (Los Angeles, Toronto), Oceania (Melbourne), and India (Sikkim) met in Kalimpong 6-8 March 2015, to discuss the topic from a variety of disciplinary viewpoints, including social history, Tibetan studies, anthropology, ethnography, religious studies, and postcolonial literature. The publisher, Heidelberg University Publishing, has included this anthology in its prestigious Heidelberg Studies on Transculturality. The history of Kalimpong, the other mountain town of Darjeeling and, more generally the entire Eastern Himalayan region, has been the focus of a specialized yet expanding scholarly field. Works center on Kalimpong (Hilker, 2005), Darjeeling (Besky, 2014; Sharma, 2011 and 2014; Warner, 2014), and the entire area of the Himalayan territories of Nepal, Sikkim, and Bhutan, as well as parts of Northern-Eastern India (Huber and Blackburn, 2012; McKay, 2007; Mullard, 2011; Phuntsho, 2013; Shneiderman, 2015). In this context, scholars note how Kalimpong and Darjeeling shared the same destiny: originally sparsely populated settlements in the foothills of the Himalayas, both villages were acquired in the nineteenth century by the English East India Company (Kalimpong was annexed in 1865 from the kingdom of Bhutan, and Darjeeling from the kingdom of Sikkim in 1835) to become British-ruled towns and ultimately hubs for commerce across British India, Sikkim, Nepal, Bhutan, Tibet, and China. Both cities showed a social hierarchical organization with colonial administrators, planters, and missionaries on top, and a wide range of settlers representing diverse Asian and Himalayan ethnicities, as well as British, German, French, and Scandinavian sojourners. Both cities would suffer in the post-colonial era from the rise of Asian nationalism, which has obstructed the once porous borders across Nepal, Tibet, Bhutan, and India. ...